Live attenuated vaccines and layered defense strategies to combat infections caused by nonencapsulated Yersinia pestis - Biryukov, Sergei S.; Klimko, Christopher P.; Dankmeyer, Jennifer L.; Toothman, Ronald G.; Shoe, Jennifer L.; Hunter, Melissa; Rill, Nathaniel O.; Talyansky, Yuli; Davies, Michael L.; Qiu, Ju; Fetterer, David P.; Bozue, Joel A.; et al. (Frontiers in Bacteriology, 2023)
Plague is an ancient disease caused by Yersinia pestis, a widely disseminated Tier 1 pathogen that poses significant public health and biothreat risks. The rapid course and high mortality of pneumonic plague limit the efficacy of antibiotic treatment and mandate the need for an effective, licensed, and readily available vaccine. New candidate vaccines are being developed; however, their efficacy in nonhuman primates, optimal vaccination schedule and immune response, duration of protection, and breadth of coverage against various virulent strains are inadequately understood. In the current work, we explored homologous and heterologous vaccination schemes using the sensitive BALB/c mouse models of bubonic and pneumonic plague challenged with Y. pestis strain C12. This strain, a derivative of wild-type strain CO92, lacks the anti-phagocytic F1 capsule yet remains highly virulent. Protection against such nonencapsulated strains has been particularly elusive.We tested the efficacy of live attenuated vaccine (LAV) derivatives of Y. pestis CO92 or C12 with a deletion of a type three secretion-associated gene (∆yscN) or of the pgm pigmentation locus and were cured of the pPst (PCP1) plasmid (CO92 pgm -pPst -). The LAVs were evaluated alone or accompanied by a dose of protein subunit vaccine (rF1V or rV).The most protective and immunogenic vaccination scheme, as tested under a variety of conditions in bubonic and pneumonic plague models, was heterologous vaccination with a LAV and the recombinant rF1V or rV protein subunit vaccine. Furthermore, in the heterologous scheme, different LAV and subunit vaccines could be substituted, affording flexibility in vaccine component selection. We also evaluated a novel intervention strategy consisting of vaccination and post-exposure antibiotic treatment. The layering of vaccination with the LAVs and postexposure treatment with streptomycin was synergistic, extending the time after Y. pestis C12 challenge when treatment remained effective and affording a sparing of antibiotic.: The current work defined effective and flexible vaccination and treatment interventions which successfully prevented lethal infection with virulent, nonencapsulated Y. pestis.